Pengaruh Jumlah Kunjungan Kapal dan Volume Kapasitas Angkut terhadap Volume Perdagangan Antar Pelabuhan Utama di Indonesia (2014-2023) - Zahirrizqon Adiba, Gilang; Indah Sari, Magreta; Zhafirah, Zahra; Azzyati, Zhafirah; Imelda, Imelda (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
This study aims to analyze the influence of Number of Ship Visits and Cargo Capacity Volume on Inter-Island Trade Volume at five major Indonesian ports: Tanjung Priok, Tanjung Perak, Belawan, Makassar, and Balikpapan. The research employs panel data from 2014–2023 consisting of 50 observations. The analysis uses panel data regression supported by the Chow Test, Hausman Test, and Lagrange Multiplier Test to determine the most appropriate model. The results indicate that the Fixed Effect Model (FEM) is the most suitable model. Empirical findings show that the number of Ship Visits significantly affects inter-island trade volume, while Cargo Capacity Volume has no significant effect. These results suggest that trade volume growth is more influenced by the frequency of ship operations than by the size of carrying capacity. The study highlights the importance of port operational efficiency and ship traffic management as key factors in improving inter-island trade performance in Indonesia.